Penerapan Green Economy terhadap Kelompok Tani Hortikultura melalui Konsep Zero Waste System Masyarakat Desa Pogalan, Magelang - Rahardjo, Budi; Giovanni, Axel; Lionora, Clarisa Alfa (Empowerment, 2024)
The residents of Pogalan Village are dominated by farmers, making the application of a green economy able to develop agriculture. In the short term, the focus of this program is to increase revenue through the concept of a zero waste system. The implementation of this Community Partnership Program is located in Pogalan Village, Pakis District, Magelang Regency. This community partnership program is carried out using the methods of socialization, education, tutorials or continuous assistance and focus group discussions. The results obtained are the understanding of farmer groups in using a zero waste system to get to a green economy. The advantage of a zero waste system has various advantages including converting waste into natural products that are environmentally friendly. Wono Mulyo farmer groups can utilize the existing waste so that it can be reused and has economic value. Community service activities are expected to continue by the Wono Mulyo farmer group to overcome other problems experienced such as marketing problems and problems in processing crops.